2018
DOI: 10.3390/min8090404
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Studies of SHMP in Reducing Negative Effects of Divalent Ions on Molybdenite Flotation

Abstract: Seawater has been considered as an alternative to freshwater for flotation. However, many ions in seawater were reported to depress molybdenite (MoS2), with the depressing mechanisms being insufficiently understood. In this study, the influence of divalent ions (e.g., Ca2+ and Mg2+) and dispersant on MoS2 flotation was systematically investigated. It was found that the detrimental effects of Ca2+ and Mg2+ on the natural flotability of MoS2 were mainly due to the attachment of formed CaMoO4 precipitates and Mg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Kaolin was acquired from Ward's Science, and quantitative X-ray diffraction (XRD) analysis showed that it contained 84 wt % kaolinite (Al 2 Si 2 O 5 (OH) 4 ) and 16 wt % halloysite (Al 2 Si 2 O 5 (OH) 4 ·2H 2 O) ( Figure 1). A D5000 X-ray diffractometer (Siemens S.A., Lac Condes, Chile) was used and the data were processed with Total Pattern Analysis Software (TOPAS) (Siemens S.A., Lac Condes, Chile).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaolin was acquired from Ward's Science, and quantitative X-ray diffraction (XRD) analysis showed that it contained 84 wt % kaolinite (Al 2 Si 2 O 5 (OH) 4 ) and 16 wt % halloysite (Al 2 Si 2 O 5 (OH) 4 ·2H 2 O) ( Figure 1). A D5000 X-ray diffractometer (Siemens S.A., Lac Condes, Chile) was used and the data were processed with Total Pattern Analysis Software (TOPAS) (Siemens S.A., Lac Condes, Chile).…”
Section: Methodsmentioning
confidence: 99%
“…In these regions, water availability may be a serious challenge and is the primary purpose for plants to reduce their water demand while avoiding significant alterations in production. A current strategy implemented in several plants is the use of seawater (see Table 1), either through prior desalination treatment by reverse osmosis, where all salts are eliminated, or by simply applying it directly, without altering the salinity [3][4][5]. The direct use of seawater entails advantages associated with environmental impact and operational costs that involve the building of a desalination plant [6]; however, the complexity of such an undertaking is the subject of constant discussion and research for engineers and scientists [3].…”
Section: Introductionmentioning
confidence: 99%
“…seawater. In the case that only molybdenite is depressed in seawater under alkaline conditions (i.e., pH 10-12), three options can be proposed: (1) the use of dispersants (e.g., sodium hexametaphosphate (SHMP)) to disperse seawater precipitates adsorbed on molybdenite surface [56,57];…”
Section: Inorganic Depressantsmentioning
confidence: 99%
“…(1) the use of dispersants (e.g., sodium hexametaphosphate (SHMP)) to disperse seawater precipitates adsorbed on molybdenite surface [56,57]; (2) the removal of problematic ions (e.g., Ca 2+ and Mg 2+ ) using Na 2 CO 3 and CaO prior to rougher/cleaner flotation [58]; and (3) the operation of rougher/cleaner flotation at a pH lower than 9.5, where Ca 2+ /Mg 2+ precipitations are limited, with alternative pyrite depressants that can act at pH < 9.5 [47].…”
Section: Organic Depressantsmentioning
confidence: 99%
“…The depression of pyrite in freshwater lime is used to bring the operation to an alkaline pH condition (>10.5), where the hydrophilic ferric hydroxide is formed. Nevertheless, this condition cannot function in seawater because the formation of solid Ca/Mg complexes strongly decreases the recovery of molybdenite [1,2] and chalcopyrite [3,4]. There is a debate as to the proper explanation of these findings in the sulphide flotation [5][6][7][8], but the recovery of water for the sustainability of the mining industry is more important.…”
Section: Introductionmentioning
confidence: 99%